STUDI PENERAPAN SISTEM MANAJEMEN KESELAMATAN PERTAMBANGAN PT. DEMPO MAJU CEMERLANG - Dipo Hadi Rahmawijaya; Fadhilah Fadhilah (Departemen Teknik Pertambangan FT UNP, 2023)
PT. Dempo Maju Cemerlang is an underground gold mining company located in Salido, Kec. Iv Jurai, kab. South Coast, Prov. West Sumatra. PT. Dempo Maju Cemerlang has not assessed the implementation of the SMKP Mining Safety Management System in accordance with KEPMEN ESDM 1827/MEM/30 2018. Therefore, it is necessary to assess the implementation of the SMKP Mining Safety Management System, Work Accident Statistics, Frequency Rate, Severity Rate and Pareto Diagram. This study aims to find out how many percent of companies in implementing the Mining Safety Management System SMKP, for the assessment using a questionnaire based on KEPMEN ESDM 1827/MEM/30 2018. The results of the questionnaire on the implementation of the Mining Safety Management System SMKP for Policy Elements 94.7%, Planning Elements 100% , Elements of Organization and Personnel 93.3%, Elements of Implementation 100%, Elements of Evaluation and Follow-up 100%, Elements of Documentation 100%, Elements of Management Review 100% and for Work Accident Statistics Frequency Rate 10.54, Severity Rate 0.